1975
DOI: 10.1177/002221947500800614
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Verbal Performance of Normal and Learning Disabled Children as a Function of Input Organization

Abstract: The purpose of this study was to extend the work of Freston and Drew (1974) which compared the free recall performance of learning disabled children as a function of organization of material and level of difficulty. A quasi-experimental design used 30 subjects classified as learning disabled and 30 normal subjects. For the normal group both material organization and level of difficulty influenced the amount of recall; for the learning disabled group, only level of material difficulty influenced recall. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
1

Year Published

1978
1978
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…The present findings conflict with those of Parker, Freston, and Drew (1975) and Freston and Drew (1974) who suggested that L/LD children as a whole do not utilize paradigmatic organization. To attempt to reconcile discrepancies, two possibilities are suggested: (1) L/LD children can use external paradigmatic organization visually, but not auditorially, or (2) the L/LD subjects in these previous studies were prevented from utilizing paradigmatic organization because of auditory perceptual or processing deficits.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The present findings conflict with those of Parker, Freston, and Drew (1975) and Freston and Drew (1974) who suggested that L/LD children as a whole do not utilize paradigmatic organization. To attempt to reconcile discrepancies, two possibilities are suggested: (1) L/LD children can use external paradigmatic organization visually, but not auditorially, or (2) the L/LD subjects in these previous studies were prevented from utilizing paradigmatic organization because of auditory perceptual or processing deficits.…”
Section: Resultscontrasting
confidence: 99%
“…To test this possibility, the design of the two available studies (Parker, Freston, & Drew 1975, Freston & Drew 1974) on the subject was modified. The major modifications involved switching from the auditory to visual pathway and ruling out visual perceptual problems.…”
Section: Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies concerned with the recall of conceptually organized word lists indicate that conceptual organization facilitates recall for good readers but not for poor readers (Parker, Freston, & Drew, 1975) and that good readers are more likely than poor readers to sort items into conceptual clusters during an orienting task prior to recall (Torgesen, Murphy, & Ivey, 1979).…”
mentioning
confidence: 99%
“…It has been suggested that rehearsal may be deficient in learning disabled children (Bauer 1977a, b, Tarver et al 1976). Since information rehearsed in short-term memory is thought to be transferred to a more permanent memory store (Atkinson & Shiffrin 1968) and learning disabled children may rehearse less effectively, a rehearsal deficit may also be responsible for slower acquisition in these children (Bauer 1977a, Parker, Cyrus, Freston, & Drew 1975.…”
mentioning
confidence: 99%